Personality And Knowledge-Sharing Behavior Among Students at Stie YPUP Makassar - Dyan Fauziah Suryadi; Mahlia Muis; Idrus Taba; Wardhani Hakim (Journal of International Conference Proceedings (JICP), 2022)
Collaborative learning is one of the most effective and popular techniques applied in building a better cooperative attitude among students in exchanging and sharing knowledge. This study aims to investigate the relationship between the Big Five Personality (extraversion, agreeableness, conscientiousness, neuroticism, openness to experience) and knowledge sharing at STIE YPUP Makassar students. This study uses a quantitative approach with 138 student respondents STIE YPUP Makassar. Data was collected through Google Form and analyzed using SPSS tool. The results of the study found that (1) all types of personality extraversion, agreeableness, openness to experience, and conscientiousness had a positive impact on knowledge-sharing behavior among students, while neuroticism had a negative impact on knowledge-sharing behavior because the character of students with unstable temperaments tended to affect student interactions in terms of share knowledge, (2) Extraversion dominant character sharing knowledge because they tend to like to live in groups and easy to socialize.Keywords: Extraversion, Agreeableness, Conscientiousness, Neuroticism, Openness to Experience, Knowledge Sharing